Agroindustrial performance and heterosis in sweet sorghum using male-sterile lines with high stem sugar content. - PEREIRA, D. A. (2022)
The objective of this study was to evaluate the performance of hybrids and the heterosis in crosses of sweet sorghum using juicy sweet male-sterile lines and fertility-restoring lines with and without sensitivity to photoperiod. Thirty hybrids and six controls were evaluated in experiments laid out in a 6 × 6 triple lattice design. The genotypes differed for all traits. The general combining ability (GCA) of the R lines affected all traits, while the GCA of the A lines only affected juice extraction, total soluble solids, and tons of Brix per hectare (TBH). The photosensitive-restoring line CMSXS5022 had the highest positive GCA estimates for the fresh mass production and TBH traits. Heterosis was significant only for days to flowering and plant height. Overall, the photoperiod-sensitive hybrids stood out. The development of male-sterile lines requires better complementarity from restoring lines to reap the benefits of heterosis.